Israel : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The estimated potential output growth decelerated from 4.9 percent in the third quarter of 2000 to 4.2 percent in the first quarter of 2001. In the Israeli context, the sharp and exogenous nature of shocks at the end of 2000 complicated the task of estimation. The paper presents potential output estimates using the Hodrick-Prescott (HP) filter and the unobserved components approach. The potential output and the nonaccelerating inflation rate of unemployment estimates have been obtained simultaneously. The statistical data are also presented in the paper.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet